A survey of a COVID-19 cluster of charter flight importation. (October 2021) - Yue, Y.; Chen, Y.; Du, X.; Jin, Y.; Hu, M.; Jiang, X.; Wang, C.; Chen, Z.; Su, L.; Chen, C.; Jiang, S.; Tuo, X.
Abstract: Objectives: Although a number of cases of importation with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection have been reported, there are still no data available concerning the characteristics in the coronavirus disease 2019 (COVID-19) cluster of charter flight importation. Here, we provide an analysis of COVID-19 cases and their close contacts who worked for the same company on a project in Karbala, Iraq, and returned back to Chengdu, China, by a charter flight. Methods: The data of imported COVID-19 cases and their close contacts were obtained from National Notifiable Disease Report System of Chinese Center for Disease Control and Prevention and field epidemiological investigation reports by Centers for Disease Control and Prevention (CDCs) in Chengdu. The information of general characteristics and laboratory findings of this cluster were collected and summarized. Results: One hundred and six (66.67%) of 159 charter flight passengers tested positive for COVID-19 before entry. Through treatment, all 159 people tested negative and meet the requirements of taking flights bound for China before boarding. However, there has been still 36 (22.64%) of them tested positive after entry. The median time from entry to confirmation was 1.0 day (Interquartile Range (IQR): 0–4.3). The Cycle threshold value (Ct value) of 36 patients' positive samples are all above 30 and most values are above 35. Conclusions: In conclusion, there is still a risk that a number of COVID-19 cases can be imported through charter flight. However, the infectivity of confirmed patients of the charter flight was considered to be low.